Myelodysplastic syndrome and extracapillary glomerulonephritis: is there a link? - Hamzi, MA; Mahtat, EM; Hassani, K; Asserraji, M; Benyahia, M; Oualim, Z (African Journal of Nephrology, 2012)
Introduction: The association of myelodysplastic syndrome and extracapillary glomerulonephritis is exceptional. Only two other cases have been reported. Reported case: A 52-year-old patient with a history of myelodysplastic syndrome developed rapidly progressive glomerulonephritis. Renal biopsy identified extracapillary glomerulonephritis. Discussion: The association of myelodysplastic syndrome with glomerulopathy is rare and often regarded as fortuitous. Only a few cases are described in literature on the subject. A relationship between the two diseases is possible but the causal link between these two diseases remains unknown. Conclusion: The notion that myelodysplastic syndrome may be associated with various glomerular nephropathies involves looking for renal disease in this haematologic disorder.